Brain cognitive performance and histopathological effects of diabetic rats induced by single and multiple dosages of streptozotocin - Titisari, Nurina; Fatimatuzzahra, Izza Nuruzzakiyah; Rahmawati, Nidya Putri; Adila, Nirmala Sekar; Fauzi, Ahmad; Razak, Intan Shameha Abdul; Samsulrizal, Nurdiana; Ahmad, Hafandi; Ahmad, Hafandi (Research Journal of Pharmacy and Technology, 2024)
Streptozotocin (STZ) is widely used to increase blood glucose levels and generate diabetic animal models. However, the dose of STZ is important as it may lead to inadequate induction of diabetes, metabolic complications, and influence the behavior of animals. Therefore, this study aimed to determine the various impacts of different STZ dosages on the brain cognitive performance associated with hyperglycemia and organ complications of diabetic rats. Animals were divided into three groups: (1) rats received a single dose of STZ (SSTZ; 55mg/kg), (2) rats received multiple doses of STZ (MSTZ; 40mg/kg) and (3) control rats received citrate buffer (CON; 0.2mL/rat) for three consecutive days intraperitoneally. Brain cognitive performance was assessed using the Y-maze test, and blood glucose level was performed weekly. The histopathological study was conducted on the pancreas, liver, kidney, and brain tissues. Results showed that animals with single and multiple doses of STZ decreased the number of entries and time spent in the novel arm of the Y-maze task. Multiple doses of STZ caused severe degenerative changes in the pancreatic islet, brain neuron apoptosis, inflammation in the liver, and tubular cell injuries. Thus, these results indicate that both single and multiple dosages of STZ influenced brain cognitive performance, which was associated with hyperglycemia and tissue degeneration in diabetic animals. © RJPT All right reserved.